“Peran Bidang Perumahan dalam Bantuan Stimulan Perumahan Swadaya (BSPS) atau Program Bedah Rumah oleh Dinas Perumahan dan Kawasan Permukiman Serta Pertanahan di Kabupaten Deli Serdang” - Muhammad Yuda Hendrawan; Muhammad Ikhsan Harahap (Pusat Riset dan Inovasi Nasional, 2023)
The Deli Serdang Regency Housing and Settlement Area Service is an agency established by the Deli Serdang Regency Government which has a vision of realizing productive, sustainable, environmentally friendly housing, including through the house renovation assistance program or PRTLH (Uninhabitable House Program) which is regularly held every year. The role of the housing sector in this implementation is to look for valid data on the houses that will be renovated. This program aims to help underprivileged people. Based on the type of research, this is descriptive research with a qualitative approach, where this study focuses on problems/phenomena that existed at the time the research was conducted, which is actual, which then describes the reality clearly and aims to find out in detail about the role of the Housing Sector in the Stimulun Assistance for Self-Help Companies or the House Renovation Program at the Department of Housing and Settlements and Land Affairs of Deli Serdang Regency. The government needs to play a greater role in providing and providing convenience and assistance for housing and residential areas for the community through the implementation of housing and area-based residential areas and community self-sufficiency so that they form a functional unit in the form of physical spatial planning, economic life and socio-culture which is able to guarantee environmental sustainability in line with the spirit of democracy, regional autonomy and openness in the order of social, national and state life.